Navigating the path of sustainability: The interconnected impact organizational resilience, community trust, and financial support - Zen, Agustian; Ali, Hapzi; Sastrodiharjo, Istianingsih; Hidayat, Wastam Wahyu (Edelweiss Applied Science and Technology, 2025)
This article aims to deepen the understanding of the emerging sustainability phenomenon in the world of business and organizations. It involves an analysis of the global business paradigm shift that increasingly emphasizes social and environmental responsibility while also exploring the challenges organizations face in managing the complex relationship between organizational resilience, community trust, and financial support. It involves identifying problems and complexities in maintaining a balance between these three aspects. The article from this study uses quantitative methods with the help of data analysis by SPSS, with the object of research being Islamic boarding schools and with the number of respondents who filled out questionnaires totaling 57 respondents from Islamic boarding school owners in Karawang. The results of the study aim to look for the influence and significance between variables. From the results and discussions above, community trust has a significant effect on sustainability, financial support has a significant effect on sustainability, and together there is a positive influence. Organizational resilience is significantly impacted by community trust, while organizational resilience is not significantly impacted by financial support. However, community trust factors, financial support, and organizational resilience all have a positive relationship. The limitation in the results of this article relates to existing variables that are present in this article. It provides an explanation of the benefits, good effects, and implications of the research results. The authenticity of the results of this study is related to the relationship between variables and objects of research.